Motivational Aspects of Information Literacy Skills Instruction in Community College Libraries - Ruth V. Small; Nasriah Zakaria; Houria El-Figuigui (College & Research Libraries, 2004)
This study explored the motivational aspects of information literacy skills instruction delivered by librarians in community college libraries. Librarians and students at seven community colleges were interviewed and observed. Involvement of faculty, use of technology, and students’ on- and off-task behaviors also were investigated. Data analyses used Keller’s ARCS Model, ACRL standards, and Small and Arnone’s Motivation Overlay for Information Skills Instruction. The majority of strategies used were to gain and maintain students’ attention. The range of strategies, rather than the number of strategies, appeared to positively affect student motivation.
Keywords: compétences; facteurs de motivation; littératie numérique